2022
DOI: 10.1186/s12905-022-01685-2
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among reproductive-age women in central Gondar zone, Northwest, Ethiopia: a population-based study

Abstract: Background Violence against women is the most widespread kind of human rights violation, and it has been linked to a wide range of consequences. The most prominent psychosocial and mental health concern that has serious effects for women's physical and mental well-being. This study assessed the prevalence and associated factors of women’s violence by intimate partner among women in the reproductive age group (15–49). Methods Multistage community-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
(57 reference statements)
3
6
0
Order By: Relevance
“…Similar findings showing that women from households in the higher wealth spectrum (richer or richest) were less likely to experience IPV and to be underweight is in line with findings from a study conducted in Bangladesh [24]. Also, the findings of the present study indicating that women who live in urban areas, those who have attained secondary education, those from middle wealth quintile households, working women and those who read newspaper and watch television, are less likely to simultaneously suffer from IPV and underweight are consistent with similar findings in Uganda and elsewhere [25][26][27][28][29]. These findings emphasize the role higher education, high PLOS GLOBAL PUBLIC HEALTH levels of socio-economic status and access to mass media play in empowering women and protecting them against human rights violations such as IPV.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings showing that women from households in the higher wealth spectrum (richer or richest) were less likely to experience IPV and to be underweight is in line with findings from a study conducted in Bangladesh [24]. Also, the findings of the present study indicating that women who live in urban areas, those who have attained secondary education, those from middle wealth quintile households, working women and those who read newspaper and watch television, are less likely to simultaneously suffer from IPV and underweight are consistent with similar findings in Uganda and elsewhere [25][26][27][28][29]. These findings emphasize the role higher education, high PLOS GLOBAL PUBLIC HEALTH levels of socio-economic status and access to mass media play in empowering women and protecting them against human rights violations such as IPV.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies reported associations within the context of cross-sectional, multivariate models adjusted for a number of covariates, using samples of women. Overwhelmingly, these studies found that higher levels of food insecurity or the presence of food insecurity was associated with multiple forms of IPV victimization (Andarge & Shiferaw, 2018; Bloom et al, 2020; Choudhary et al, 2020; Diamond-Smith et al, 2019; Field et al, 2018; Fong et al, 2016; Getinet et al, 2022; Gibbs, Corboz et al, 2018; Haque et al, 2020; Hatcher et al, 2021; Laraia et al, 2022; Leite de Moraes et al, 2016; Lim et al, 2019; Mahfouz et al, 2021; Montgomery et al, 2015; Naved et al, 2018; Postmus et al, 2021; Ricks et al, 2016; Willie et al, 2018). A few studies found similar results with slightly different conceptualizations of food insecurity; for example, one study found that more worry about the ability to buy food was associated with IPV victimization (Lee et al, 2021), and another found that IPV was associated with less efficacy in obtaining resources including food (Lee & DePrince, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ∼35% of respondents considered that ‘forcing your partner to have sex is not rape’, and ∼24% considered that ‘forcing sex with someone you know is not rape’ either ( Andersson et al , 2007 ). A study based in North-West Ethiopia suggests a prevalence rate of intimate partner violence (IPV) of ∼49% among women of reproductive age ( Getinet et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%